Efeito de irrigação e adubação nitrogenada nas characterísticas agronômicas de milho doce - de Souza, Epitácio José [UNESP]; da Cunha, Fernando França; Magalhães, Fernando Fagner; da Silva, Thiago Ramos; dos Santos, Osvaldir Feliciano (FapUNIFESP (SciELO), 2015)
Irrigation and nitrogen fertilization are management practices that have positive results for the corn crop. This study aimed at evaluating the effect of nitrogen fertilization and irrigation on agronomic traits of sweet corn. Two experiments were carried out in two crop seasons (winter/spring and summer/autumn), in a split-plot design, with the main plots consisting of four irrigation levels (50 %, 75 %, 100 % and 125 % of the crop evapotranspiration - ETc) and subplots consisting of four nitrogen doses (0 kg ha-1, 100 kg ha-1, 200 kg ha-1 and 300 kg ha-1), applied at the V3 and V8 stages, via urea, in a randomized blocks design experiment, with four replications. Leaf nitrogen content, root depth, plant height, stem diameter, ear yield and water use efficiency were evaluated. In the winter/spring season, nitrogen fertilization did not affect yield, while in the summer/autumn season the dose that maximized yield was 300 kg ha-1. Sweet corn showed better results when irrigated with replacements of 50 % and 125 % of ETc, respectively in the summer/autumn and winter/spring seasons.
Effect of irrigation and nitrogen fertilization on agronomic traits of sweet corn
Keywords: Drip irrigation; Specialty corn; Water use efficiency; Zea mays var. saccharata sturt